2017
DOI: 10.5944/ap.14.2.20024
|View full text |Cite
|
Sign up to set email alerts
|

Cultura de conciliación y conflicto trabajo/familia en trabajadores con turnos laborales

Abstract: ResumenEl número de personas que compaginan de forma simultánea el trabajo con las responsabilidades familiares ha aumentado en España de forma considerable en éstas tres últimas décadas. Entre otras razones esto puede ser consecuencia del aumento de familias monoparentales, de la incorporación de la mujer al mundo laboral y emprendedor, de la existencia de parejas con dobles carreras profesionales y con diferentes horarios. Esta influencia recí-proca entre los contextos laboral y no laboral puede traducirse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
3
0
7
Order By: Relevance
“…Our results first indicate the need for scholars to rethink how we evaluate the effectiveness of work-home practices. To date, studies on work-home practices have indicated that work-home practices are not always used when available (McDonald et al, 2005; Allen et al, 2013), and that, in the case of use, the use is not always associated with the intended positive effects on employee outcomes (e.g., Butts et al, 2013). We argue that not using available practices does not have to indicate a failed implementation policy neither does use of these practices imply a successful implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results first indicate the need for scholars to rethink how we evaluate the effectiveness of work-home practices. To date, studies on work-home practices have indicated that work-home practices are not always used when available (McDonald et al, 2005; Allen et al, 2013), and that, in the case of use, the use is not always associated with the intended positive effects on employee outcomes (e.g., Butts et al, 2013). We argue that not using available practices does not have to indicate a failed implementation policy neither does use of these practices imply a successful implementation.…”
Section: Discussionmentioning
confidence: 99%
“…How working time is arranged has become a basic organising factor in societies today and takes on a societal aspect, since a person’s working day is tied inextricably to the remaining social time, including the time devoted to the family (Ortiz, 2014; Prieto, 2007; Prieto et al, 2008; Torns, 2015). The poor fit between the working and non-working spheres has been a source of conflict owing to the different roles played by individuals (Chou and Cheung, 2013; Pérez-Rodríguez et al, 2017; Thomas and Ganster, 1995). It is also due to the fact that time is a limited resource that is often distributed in an incompatible manner at the ‘work–family interface’ (Pérez Pérez et al, 2015: 16).…”
Section: Social Habits and Work–life Balancementioning
confidence: 99%
“…In industrialised societies, the disposition of working time has traditionally been configured as the strategic and organisational prerogative of companies, but it is also one of the issues that has received most attention as a way to improve the quality of employment and its relationship with other spheres of people’s lives, optimising welfare and balance between the demands of family and work (Kinnunen et al, 2005; Pérez Rodríguez et al, 2017). New human resource management has identified changes in workers’ preferences, which has diversified working time patterns (Campbell, 2017; Lee, 2004; Lee et al, 2007; Messenger, 2004) and introduced alternative welfare benefits through the ‘right to request’ variations in employment contracts (Fagan et al, 2014:8).…”
Section: Social Habits and Work–life Balancementioning
confidence: 99%
“…La cultura trabajo-familia, como relación conceptual multidimensional ha sido estudiada desde diversas perspectivas (Amstad et al, 2011;Pérez et al, 2017) relacionando el contexto de trabajo con los diversos roles familiares que hombres y mujeres desarrollan más allá de sus desempeños laborales (Warren y Johnson, 1995;Allen, 2001;). Este constructo relacional busca conciliar la complejidad del quehacer laboral con la vida de familiar en sus diversas dimensiones (Thompson et al, 1999) y pone de manifiesto que la relación trabajo y familia agudiza tensiones si las jornadas son extensas e impide a los trabajadores compatibilizar vida laboral con los tiempos requeridos por la familia (Jansen et al, 2010;McMillan et al, 2011).…”
Section: Introductionunclassified